(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Phacogenic glaucoma is a form of secondary glaucoma that occurs due to pathological changes in the lens, most often with hypermature cataracts or after their surgical removal. The study included 45 consecutive eyes of 45 patients with phacolytic glaucoma who underwent surgery between January 2025 and December 2025 and who received at least one year of follow-up. Of the 45 eyes, 17 underwent extracapsular cataract extraction (ECE) with primary implantation of a posterior chamber intraocular lens (IOL) (Group 1). The remaining eyes (n = 28) underwent only extracapsular cataract extraction (group 2) due to satisfactory aphakic vision in the contralateral eye. Of the 45 patients diagnosed with glaucoma or suspected of having glaucoma, 35 (7.4%) had secondary glaucoma. The mean age at presentation was 52 ± 17 years, and the male to female ratio was 1.5:1. The most common cause was lenticular glaucoma (25 cases, 32.8%), followed by neovascular 10 (20.3%), steroid 16 (16.3%), traumatic 14 (14.4%), postvitrectomy 7 (3.2%), uveitis 11 (2.1%), pseudophakic 10 (1.9%), aphakic 8 (1.5%), postkeratoplasty 5 (0.9%), and other causes 35 (6.6%).